IFLUENCE OF FUNCTIONAL FOOD PRODUCT ON SERUM FATTY ACID COMPOSITION IN HYPERLIPIDEMIC RATS - I. M. Chernukha; E. A. Kotenkova (Пищевые системы)
A special area in the rapidly growing range of food products is occupied by specialized and functional products, especially for certain categories of citizens. In addition to confirming their biocorrective properties, it’s necessary to balance protein, fat and carbohydrates contents as well as the availability of essential nutrients. The developed meat product based on porcine hearts and aorta was characterized by a high protein content (17.53±0.95%), with a low fat content (3.82±0.13%), the atherogenic index was 0.43. According to in vivo study results, it was shown that the introduction of developed product during 42 days into the diet of hyperlipidemic rats lead to a decrease in the relative content of saturated fatty acids by 21.1%(P<0.05), mainly due to palmitic fatty acid reduction by 42.0% (P<0.05) compared with the control. The observed modifications of serum fatty acid composition resulted in the reduction of atherogenic index by 43.3% (P<0.05). The revealed positive dynamics of lipid metabolism recovery in hyperlipidemic rats makes it possible to recommend the developed product as a component of diet therapy, concomitant to the main treatment, for persons with risk of cardiovascular diseases, in particular, due to dyslipidemias.